A SENSITIVE ASSAY FOR NON-SPECIFIC N-METHYLTRANSFERASE ACTIVITY IN RAT TISSUES BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY ELECTROCHEMICAL DETECTION - Dawan Shimbhu; Kohichi Kojima; Toshiharu Nagatsu (Universitas Gadjah Mada, 2002)
Phenylethanolamine N-methyltransferase (PNMT) and non-specific N -methyltransferase (EC 2.1.1.28) catalyze the N-methylation of aromatic amines. PNMT is specific for phenylethanolamines such as noradrenaline (NA). and catalyzes the step in catecholamine biosynthesis, forming adrenaline (AD) from NA. PNMT activity is high in adrenal gland, whereas non-specific N-methyltransferase is distributed in various tissues such as the lungs. Borchardt et al. first reported a method to detect PNMT activity by high-performance liquid chromatography electrochemical detection (HPLC-EICD), which could demonstrate the activity only in the adrenal medulla and hypothalamus. Recently, Troeewicz et al. reported a highly sensitive assay method for PNMT using HPLC-EICD by which the activity in all regions of rat brains could be measured. The activity of non-specific N-methyltransferase in brain regions and peripheral tissues of the rat could be detected by a radioassay. However, there has been no repot on an assay method for non-specific N-methyltransferase using HPLC-EICD. In this paper, we describe a highly sensitive assay procedure for the activity of non-specific N-methyltransferase by high-performance reversed-phase ion pair chromatography with electrochemical detection. By this method, the non-specific N-methyltransferase activity could be determined in various rat brain regions and peripheral tissues.